The Correlation Between English Study Program Students’ Habits in Reading Digital English Comics by Using Webtoon Application and Their Vocabulary Mastery - Adhisty Shenia Auliandri Putri; Supriusman Supriusman; Novitri Novitri (Journal of Education Technology Information Social Sciences and Health, 2026)
This research investigates the correlation between English study program students’ habits in reading digital English comics by using Webtoon application and their vocabulary mastery. The growing popularity of digital comic platforms like Webtoon and their increasing use by students for both leisure and language exposure provided the context for this research. The study was conducted at the English study program of Universitas Riau. Data were collected through a questionnaire on reading digital English comics habits and a vocabulary mastery test, then analyzed using Spearman’s Rho correlation coefficient in IBM SPSS 25. The descriptive analysis revealed that the mean score was 3.39 for students' reading habits and 0.80 for their vocabulary mastery. The statistical analysis yielded a Spearman’s Rho correlation coefficient of -0.130 and a p-value of 0.492, which is greater than the 0.05 significance level. Therefore, the null hypothesis was accepted. This led to the conclusion that there is no statistically significant correlation between the English study program students’ habits in reading digital English comics by using Webtoon application and their vocabulary mastery.